TYPIFICATION OF NAMES IN ERIOCAULON IN THE FLORA OF THAILAND AND FLORA OF CAMBODIA, LAOS AND VIETNAM - Souladeth, P.; Prajaksood, A.; Parnell, J. A. N.; Newman, M. F. (Edinburgh Journal of Botany, 2016)
Lectotypes are designated for eight names in Eriocaulon in tropical Asia, namely E. alatum, E. hamiltonianum, E. hookerianum, E. infirmum, E. lanigerum, E. nautiliforme, E. nigrum and E. ubonense. Additional information on the lectotype of Eriocaulon quinquangulare is given.
Keywords: Eriocaulon; nomenclature; Southeast Asia; typification